THE GROWTH AND CHARACTERIZATION OF CRYSTALS OF HUMAN-IMMUNODEFICIENCY-VIRUS (HIV) REVERSE-TRANSCRIPTASE - Jones, E; Stuart, D; Garman, E; Griest, R; Phillips, D; Taylor, G; Matsumoto, O; Darby, G; Larder, B; Lowe, D; Powell, K; Purifoy, D; et al. (1993)
Extensive studies on the crystallization of HIV-1 reverse transcriptase (RT) have yielded several crystal forms, two of which show diffraction to minimum Bragg spacings of 6 Å or better. Type 1 crystals belong to the space group P212121 with unit cell dimensions a = 147 A ̊, b = 190 A ̊ and c = 182 A ̊. Crystal density measurement indicate a very high crystal solvent content of 77% consistent with the presence of two RT heterodimers (66k/51k) per crystallographic asymmetric unit. These crystals are suitable for a low resolution determination of the apoenzyme structure. The second well ordered crystal form (space group P4222 with unit cell dimensions a = b = 120 A ̊, c = 320 A ̊) results from the co-crystallization of RT heterodimer and a double-stranded DNA oligonucleotide. Crystal density measurements again yield a relatively high value for the solvent content (7%; one RT heterodimer per crystallographic asymmetric unit) and elemental analysis indicates that one DNA oligonucleotide is associated with each RT heterodimer. This is consistent with each heterodimer possessing a single, competent, active site. © 1993.